Social Work Research on Immigrants: A Content Analysis of Leading Journals from 2007 to 2016. Issue 2 (11th April 2021) - Diaz-Strong, Daysi Ximena; Roth, Benjamin J.; Velazquillo, Angelica; Zuch, Michael
: International migration has emerged as one of the most controversial phenomena of the 21st century. The complexity and implications of global migrations require that social work practitioners and researchers have access to data-informed research and critical analyses. However, the content of recent social work research on international migration has not been adequately examined to assess whether and to what extent this substantive area is being addressed. This article explores how social work research published in five leading social work journals— Health & Social Work, Research on Social Work Practice, Social Service Review, Social Work, and Social Work Research —is advancing our understanding of international migration and where it may be lacking. Focusing on articles published between 2007 and 2016, the authors analyzed content addressing immigrants and refugees. The content analysis indicates that social work research is making a strong contribution in the area of mental health but is not adequately addressing critical dimensions of stratification, including race, ethnicity, and legal status. Authors also find ambiguity in how "immigrant" is defined and in the generation(s) addressed. Authors argue that maximizing social work's contributions requires offering more nuanced definitions of the immigrant populations addressed and paying greater analytical attention to dimensions of inequality.